2019
DOI: 10.1016/j.jamcollsurg.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Resuscitation Consideration: Sex Matters

Abstract: Background-Sex dimorphisms in coagulation have been recognized but whole blood assessment of these dimorphisms and their relationship to outcomes in trauma have not been investigated. This study characterizes the viscoelastic hemostatic profile of severely injured patients by sex and examines how sex-specific coagulation differences affect clinical outcomes, specifically massive transfusion (MT) and death. We hypothesize that severely injured females are more hypercoagulable and thus, have lower rates of MT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 36 publications
2
65
1
Order By: Relevance
“…In addition to environmental factors and ethanol, sex and age also contribute to discrepancies in coagulation profiles. Recent work has demonstrated a mortality impact of sex differences in coagulation profiles with females demonstrating a more hypercoagulable profile and survival benefit in the setting of depressed clot strength 184 . As discussed above, investigations of VEM in pediatric patients are relatively limited in comparison to adults; extrapolating findings from adult studies to the care of pediatric trauma patients should be done with caution.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to environmental factors and ethanol, sex and age also contribute to discrepancies in coagulation profiles. Recent work has demonstrated a mortality impact of sex differences in coagulation profiles with females demonstrating a more hypercoagulable profile and survival benefit in the setting of depressed clot strength 184 . As discussed above, investigations of VEM in pediatric patients are relatively limited in comparison to adults; extrapolating findings from adult studies to the care of pediatric trauma patients should be done with caution.…”
Section: Resultsmentioning
confidence: 99%
“…Schoenberg et al demonstrated that women tend to die soon after trauma and therefore would not have time to develop complications such as atrial fibrillation . It has also been shown in several studies that women have a more hypercoagulable profile and greater hemodynamic tolerance to shock than men, leading them to need less fluid resuscitation . In a 59‐year meta‐analysis looking specifically at the role of sex in atrial fibrillation, Michelena et al found higher rates of lone atrial fibrillation in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Current transfusion protocols in trauma do not use sex-specific guidelines, and even the TEG based resuscitation protocols were established in a predominantly male population. 25 Therefore, it is somewhat unsurprising that despite using resuscitation protocols guided by nearly real-time data on coagulation profiles, there was no sex difference in the amount of blood product given in the study by Coleman et al 20 Females may be overly resuscitated with certain blood products under current protocols, which can have significant consequences including thromboembolic events. Prior to modern DCR, a greater amount of crystalloids were given in massive hemorrhage, and aggressive volume resuscitation with crystalloids can lead to coagulopathy, for which females have twice the mortality.…”
Section: Sex and Gender Differences In Transfusion Protocolsmentioning
confidence: 99%
“…For instance, sex differences in physiology as fundamental as the relative quantity of proteins comprising apheresis platelets have been observed, 19 and we know there are also clinically significant sex differences in hemostatic response to trauma, with females being more hypercoagulable. 20,21 The prevailing modern resuscitation strategy in traumatic hemorrhage, which was borne from military studies predominantly using young men, is called Damage Control Resuscitation (DCR) and involves giving blood products early and aggressively in high ratios (1:1:1 or 1:1:2 of plasma: platelets: RBC) while limiting crystalloid use. At least 2 studies have found mortality differences based on recipient sex, and the ratio of blood products they are resuscitated with.…”
Section: Sex and Gender Differences In Transfusion Protocolsmentioning
confidence: 99%
See 1 more Smart Citation